1999
DOI: 10.1038/sj.cgt.7700012
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-macrophage colony-stimulating factor (GM-CSF) secreted by cDNA-transfected tumor cells induces a more potent antitumor response than exogenous GM-CSF

Abstract: Clinical cancer gene therapy trials have generally focused on the transfer of cytokine cDNA to tumor cells ex vivo and with the subsequent vaccination of the patient with these genetically altered tumor cells. This approach results in high local cytokine concentrations that may account for the efficacy of this technique in animal models. We hypothesized that the expression of certain cytokines by tumor cells would be a superior immune stimulant when compared with local delivery of exogenous cytokines. Granuloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…Indeed, the more toxic the treatment the less the secretion of GM-CSF by the transduced tumor cells and the worse the therapeutic response observed. Moreover, in agreement with the work of Shi et al (35) but contrary to Kurane et al (36), we observed that the GM-CSF protein expressed by tumor cells after gene transfer was a superior stimulant than exogenous GM-CSF given in the tumor microenvironment by repeated injections or osmotic minipumps (8). This could be explained in part by the short half-life (few hours) of recombinant GM-CSF (37).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the more toxic the treatment the less the secretion of GM-CSF by the transduced tumor cells and the worse the therapeutic response observed. Moreover, in agreement with the work of Shi et al (35) but contrary to Kurane et al (36), we observed that the GM-CSF protein expressed by tumor cells after gene transfer was a superior stimulant than exogenous GM-CSF given in the tumor microenvironment by repeated injections or osmotic minipumps (8). This could be explained in part by the short half-life (few hours) of recombinant GM-CSF (37).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, frequent or continuous cytokine administration would be required at the immunization sites in order to overcome these limitations, and is expected to result in a dissimilar pharmacokinetic profile and a less durable effect than cytokine-secreting hydrogel with steady secretion. There have been some reports which have demonstrated that immunization with GMCSF-secreting cells yielded superior anti-tumor efficacy, as compared to the co-administration of rGMCSF and irradiated, non-cytokine secreting cells [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have revealed clear anti-tumor and immuno-modulating effects of GM-CSF gene therapy in treating renal cell carcinoma, melanoma, lung cancer, bladder cancer, and hematological malignancies. [20][21][22] GM-CSF-secreting tumor cells have been found to stimulate potent, specific, and long-lasting anti-tumor immunity, partly because GM-CSF stimulates the proliferation and differentiation of antigen-presenting cells. 23,24 Although the anti-tumor effects of GM-CSF alone were insufficient to eradicate tumors, our carrier cell experiments demonstrated that animals could be completely cured with injection of carrier cells co-infected with AdE3-IAI.3B and AxCAmGM-CSF after immunization with adenovirus.…”
Section: Discussionmentioning
confidence: 99%